Accurate and Computational: A review of color reproduction in Full-color 3D printing. (1st November 2021) - Yuan, Jiangping; Chen, Guangxue; Li, Hua; Prautzsch, Hartmut; Xiao, Kaida
Graphical abstract: Highlights: Shows the state of the art of color reproduction methods in full-color 3D printing. Judges the suitability of current methods expanded to a universal color standard. Cases analysis of three key issues for achieving accurate full-color 3D printing. States a potential theoretical framework suitable for various 3D printing materials. Abstract: As functional 3D printing becomes more popular with industrial manufacturing applications, it is time to start discussing high-fidelity appearance reproduction of 3D objects, particularly in faithful colors. To date, there is only limited research on accurate color reproduction and on universal color reproduction method for different color 3D printing materials. To systematically understand colorization principles and color transmission in color 3D printing, an exhaustive literature review is stated to show the state of the art of color reproduction methods for full-color 3D printing, such as optical parameter modeling, colorimetric difference evaluation, computer aided colorization and voxel droplet jetting. Meanwhile, the challenges in developing an accurate color reproduction framework suitable for different printing materials are fully analyzed in this literature review. In full-color 3D printing, coloring, rendering and acquisition constitute the core issues for accurate color reproduction, and their specific concepts are explained in concrete examples. Finally, the future perspectives of a universal color reproduction framework for accurate full-color 3D printing are discussed, which can overcome the limitations of printing materials, combined with computational boundary contoning.